PENGARUH PEMANFAATAN PANGAN LOKAL DENGAN METODE PIS-PK UNTUK MENINGKATKAN STATUS GIZI BALITA - Yosephina Maria Hawa Keytimu; Maria Susana Ine Nona Ringgi; Yustina Y. Guru (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2022)
Malnutrition  is experienced by children in Indonesia due to inadequate nutritional intake and the presence of infectious diseases and a combination of both. These problems affect the level of intelligence, increase in infectious diseases and morbidity and mortality. Malnutrition that occurs in Magepanda District is caused by socioeconomic disparities, geographic conditions, suboptimal feeding, food insecurity, maternal knowledge, parenting patterns, lack of cross-sectoral cooperation, maternal age and maternal education. Preliminary studies found that young mothers used to eat unhealthy snacks for their children and believed that poor nutrition was not harmful to their children's health. Regarding parenting, mothers prefer to leave their children to be cared for by their parents because they are busy working in the fields and some migrate to other areas, besides that, mother-in-law dominates in daily food arrangements.This study aims to determine the effectiveness of training on the use of local food using the PIS-PK method to improve the nutritional status of children under five. Methods: The research method used was pre-experimental with one group pretest and posttest design. The research subjects consisted of 1 group, namely the intervention group without the control group. The intervention group was given training using the PIS-PK approach. Assessment in the intervention group was carried out before and after training (pretest and posttest). The results of the study obtained a sig value of 0.000 which is smaller than 0.05, meaning that there is an influence between training on the use of local food and the PIS-PK method on improving the nutritional status of children under five. Conclusion: that training on the use of local food using the PIS-PK method has a positive impact because it can increase body weight and nutritional status of toddlers. Kata kunci       : Local food, Mallnutrition, PIS-PK